Analysis of 17p11.2 chromosome region rearrangements in CMT1 patients from Ukraine - Hryshchenko, N.V.; Livshits, L.A. (Цитология и генетика, 2009)
Two intercomplementary methods of 17p11.2 duplication/deletion identification have been elaborated: STR allelic variants analysis and direct PMP22 gene dosage measuring by means of quantitative Real Time PCR. It has been carried out detection and analysis of 17p11.2 chromosome region rearrangements in CMT1 patients from Ukraine. It has been registered the high level of de novo cases with 17p11.2-duplication. It has been shown the 17p11.2 chromosome region duplication/deletion association with CMT1A and HNPP clinical phenotypes which may be used in differential diagnosis of this type of CMT polyneuropathy. Проведена детекция и анализ хромосомных перестроек области 17p11.2 у пациентов с болезнью ШаркоМари-Тус (ШМТ) из Украины. Разработаны два взаимодополняющих метода идентификации дупликаций/делеций в области 17p11.2: анализ аллельных вариантов STR локусов и прямой анализ дозы гена РМР22 с использованием ПЦР в реальном времени. Выявлен высокий уровень de novo дупликаций в указанном хромосомном регионе. Показана ассоциация дупликаций/делеций в области 17p11.2 с клиническими фенотипами ШМТ1А и HNPP, что может быть использовано для дифференциальной диагностики упомянутых типов полиневропатии ШМТ. Проведено детекцію та аналіз хромосомних перебудов ділянки 17p11.2 у пацієнтів з хворобою Шарко-Марі-Тус (ШМТ) з України. Розроблено два взаємодоповнюючі методи ідентифікації дуплікацій/делецій у ділянці 17p11.2: аналіз алельних варіантів STR-локусів та прямий аналіз дози гена РМР22 із використанням ПЛР у реальному часі. Виявлено високий рівень de novo дуплікацій цієї хромосомної ділянки. Показано ассоціацію дуплікацій/делецій у ділянці 17p11.2 із клінічними фенотипами ШМТ1А та HNPP, що може бути використано для диференційної діагностики даних типів поліневропатії ШМТ.